Topographic cues guide the attachment of diatom cells and algal zoospores - Xiao, Linlin; Grunze, Michael; Rosenhahn, Axel (Biofouling, 2018)
Surface topography plays a key role in the colonization of substrata by the colonizing stages of marine fouling organisms. For the innovation of marine antifouling coatings, it is essential to understand how topographic cues affect the settlement of these organisms. In this study, tapered, spiked microstructures and discrete honeycombs of varying feature dimensions were designed and fabricated in order to examine the influence of topography on the attachment of zoospores of the green macroalga Ulva linza and cells of the diatom (microalga) Navicula incerta. Contrasting results were obtained with these two species of algae. Indeed, the preferred location of cells of N. incerta was dominated by attachment point theory, which suggested a positive correlation between the density of cells adhering and the amount of available attachment points, while the settlement of spores of U. linza was mainly regulated by both Wenzel roughness and local binding geometry.